Sperm–Particle Interactions and Their Prospects for Charge Mapping. Issue 9 (19th July 2019) - Magdanz, Veronika; Gebauer, Johannes; Sharan, Priyanka; Eltoukhy, Samar; Voigt, Dagmar; Simmchen, Juliane
Abstract: In this article, a procedure to investigate sperm charge distribution by electrostatic sperm–particle interactions is demonstrated. Differently chargedparticles are fabricated and their attachment distribution on the bovine sperm membrane is investigated. The sperm‐particle attachment sites are observed using bright field and cryo‐scanning electron microscopy combined with energy‐dispersive X‐ray analysis. The findings suggest that the charge distribution of the sperm membrane is not uniform, and although the overall net charge of the sperm cell is negative, positively charged areas are especially found on the sperm heads. The newly developed method is used to investigate the dynamic charge distribution of the sperm cell membrane upon maturation induced by heparin, as a representation of the multitude of changes during the development of a sperm. Abstract : In this article, the attachment of differently charged microparticles to bovine sperm cells is investigated. The binding of positively and negatively charged particles to different distinct regions of the sperm's surface is promising for charge mapping, which could give insight into the dynamic change of surface charge, an important indicator for changes during a sperm's development.